The Associations Between Severity Of Symptoms, D-Dimer and Incidence of ARDS In COVID-19 - Herani Mutia Riandini; Fajrinur Syaran; Syamsul Bihar; Putri Chairani Eyanoer (Indonesian Society of Respirology (ISR), 2022)
Background: Severe acute respiratory injury caused by COVID-19 (ARDS) is a serious emerging complication. ARDS results from a cytokine storm that occurs in the second week of the disease course and acute-onset hypoxemia can be seen with bilateral infiltrates on chest radiograph. This study aimed to relate the severity of symptoms and D-dimer level to the incidence of ARDS in COVID-19 at H. Adam Malik Hospital as the referral center for COVID-19 in North Sumatra. Method: This was a descriptive study with a retrospective cohort design. The sample of this study was secondary data from medical records of positive RT-PCR COVID-19 patients from November 2020 to April 2021. The inclusion criteria were patients with moderate to critical COVID-19 cases with D-dimer examination taken from the first day of admission. Subjects were then followed up until discharge from the hospital to assess for ARDS episodes which were confirmed by the results of PaO2/FiO2 in arterial blood gases and bilateral infiltrations in chest X-Ray. The exclusion criteria were incomplete medical records. Results: The association between the severity of symptoms and the incidence of ARDS, 1 of which was found to be moderate, 19 cases were severe and 20 were critical. However, there was a statistically significant correlation between the severity of symptoms and the incidence of ARDS (P=0.0001). Conclusion: There was a significant correlation between the severity of symptoms and the D-dimer value on the incidence of ARDS.